BAHASA INGGRIS - Yusnita; Isna, Nuzulul (STKIP Siliwangi, 2025)
Reading is one of the English skills that has a significant role in helping students acquire English better and succeed in the academic field. Unfortunately, most students still struggle with reading comprehension, especially descriptive text. The students can still not scan what descriptive text tells about, although they have read it repetitively. This study is proposed to discover students’ difficulties in reading descriptive text. The method is qualitative design with 35 subjects. The data were collected through interviews and observation. The result of this study showed that the difficulties in reading comprehension faced by students are due to the fact that the length of the text can frustrate students to grasp the meaning. Secondly, there is a lack of vocabulary mastery; most students are poor in vocabulary mastery and face difficulty gaining information on descriptive text when they find unfamiliar words. Thirdly, when reading without strategies, most students only read the text without implementing the appropriate methods to comprehend it better. Fourthly, there is a lack of prior knowledge: most students do not have background knowledge of the topic they read. Lastly, limited reading practice, since students only practice reading when English subjects have limited reading references.